2022
DOI: 10.1038/s42003-022-03911-x
|View full text |Cite
|
Sign up to set email alerts
|

TOB1 attenuates IRF3-directed antiviral responses by recruiting HDAC8 to specifically suppress IFN-β expression

Abstract: Interferon regulatory factor 3 (IRF3) is a key transcription factor required for the secretion of type I interferons (IFN-α/β) and initiation of antiviral immune response. However, the negative feedback regulator of IRF3-directed antiviral response remains unknown. In this study, we demonstrated that viral infection induced the interaction of the transducer of ERBB2.1 (TOB1) with IRF3, which bound to the promoter region of Ifnb1 in macrophages. TOB1 inhibited Ifnb1 transcription by disrupting IRF3 binding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…TOB1 -knockout leads to increased protein levels of RIG-I and MDA5, directly enhancing the innate immune signal pathway and its downstream transmission, including the production of IFN and high expression of ISGs. A recent study has also reported that TOB1 negatively regulates IFN-β by inhibiting its transcription in macrophages by disrupting the binding of IRF3 and recruiting HDAC8 to the IFN-β1 promoter region [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…TOB1 -knockout leads to increased protein levels of RIG-I and MDA5, directly enhancing the innate immune signal pathway and its downstream transmission, including the production of IFN and high expression of ISGs. A recent study has also reported that TOB1 negatively regulates IFN-β by inhibiting its transcription in macrophages by disrupting the binding of IRF3 and recruiting HDAC8 to the IFN-β1 promoter region [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, within immune cells, TOB1 presents a distinct facet. TOB1 suppresses T cell proliferation, preserves T cell quiescence, dampens the differentiation of CD4 + T cells into Th1/Th2 subsets, and hampers macrophage activation (14,(23)(24)(25)(26)(27). Consequently, a comprehensive understanding of TOB1 expression and function within the gastric cancer immune microenvironment is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, TOB1 plays a role in adaptive immunity by inhibiting T cell proliferation and differentiation, thereby maintaining T cells in a quiescent state (22). In the context of innate immunity, TOB1 suppresses the production of IFN-b in macrophages, favoring viral replication (26). Therefore, we speculated that TOB1 acts as a negative regulator in immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…TOB1 attenuates IRF3-directed antiviral responses by recruiting HDAC8 to specifically suppress IFN-β expression in virus-infected macrophages. TOB1 deficiency enhanced antiviral response and suppressed viral replication in vivo ( Yu et al., 2022 ). The present study aimed to understand the functional role of B. tabaci TLR3 and TOB1 in ChiLCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Toll receptors induce interferons to confer antiviral resistance in vertebrates ( Lester and Li, 2014 ). TOB1 attenuates IRF3-directed antiviral responses by recruiting HDAC8 in virus-infected macrophages ( Yu et al., 2022 ). However, the role of TLR3 and TOB1 in the virus transmission by B. tabaci or any other arthropods is not known.…”
Section: Introductionmentioning
confidence: 99%